La crypte de l’abbaye Saint-Séverin à Château-Landon (Seine-et-Marne) : analyse architecturale d’un édifice de l’an Mil - Stéphane Büttner; Fabrice Henrion; Claude de Mecquenem; Bénédicte Palazzo-Bertholon (Archéologie Médiévale)
In 1995, prior to a building project, a rescue excavation was programmed on the Saint-Séverin Abbey site in Château-Landon, the crypt of which was hitherto known to only a few specialists and local scholars. The first archaeological assessment has shown the importance of this edifice, adding elements to the rather sparse corpus of monumental architecture in the environs at the beginning of the second millennium. Due to the degraded state of the masonry, the construction materials used have been widely documented by specialists. These results highlight the interdisciplinary approach essential to archaeological standing building studies. This work throws new light on the re-use of materials within the edifice which, beyond statement of fact, reveals the symbolic value of the materials forming the sacred enclosure of the crypt.